A Reconsideration of the Diaconate - Ross, J. M. (Scottish journal of theology, 1959)
The Report on ‘Relations between the Anglican and Presbyterian Churches’ has given rise to much discussion of the Episcopate; but it may not be unprofitable if some study were to be given, in the churches of both traditions, to the true nature of the diaconate, especially as the Report invites the Anglican churches to consider setting apart lay persons for some measure of pastoral responsibility for their fellow-Christians, ‘possibly through a reform of the diaconate’.